2011
DOI: 10.5301/hip.2011.8409
|View full text |Cite
|
Sign up to set email alerts
|

Subsidence of the Corail Femoral Component in the Elderly. A Retrospective Radiological Review

Abstract: 206 patients age 70 years or older who underwent uncemented total hip arthroplasty (THA) using the Corail stem were studied. Radiographs taken post operatively and at one year were measured for subsidence of the stem. 13 patients had subsidence of the femoral stem of more than 2 mm. 5 of these were associated with fractures (mean age 78.06 years--average subsidence 14.52 mm), while 8 did not have associated fractures (mean age 77.43 years--average subsidence 4.99 mm). These 13 patients were then followed up fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…The Active stem subsided to a greater extent than the HAC stem during the first 3 months, but thereafter no further subsidence was seen, suggesting that the osseointegration was not compromised by the early subsidence. The pattern of subsidence seen for the Active stem was similar to the pattern of subsidence observed in RSA studies with other uncemented collarless prostheses with excellent long-term results, for example the Cone stem ( Strom et al 2006b ), the CLS stem ( Strom et al 2007 ), and the Corail stem ( Campbell et al 2011 , Faisal et al 2011 ).…”
Section: Discussionsupporting
confidence: 78%
“…The Active stem subsided to a greater extent than the HAC stem during the first 3 months, but thereafter no further subsidence was seen, suggesting that the osseointegration was not compromised by the early subsidence. The pattern of subsidence seen for the Active stem was similar to the pattern of subsidence observed in RSA studies with other uncemented collarless prostheses with excellent long-term results, for example the Cone stem ( Strom et al 2006b ), the CLS stem ( Strom et al 2007 ), and the Corail stem ( Campbell et al 2011 , Faisal et al 2011 ).…”
Section: Discussionsupporting
confidence: 78%
“…Comparison of previous study (Faisal et al18 ) with current study. Effect of various variables on subsidence.…”
mentioning
confidence: 70%
“…A previous study from our centre reported on 206 patients of age 70 years or older who underwent uncemented total hip arthroplasty (THA). 18 Radiological assessment was done postoperatively and at 1 year demonstrated a subsidence rate (>2 mm) of 6.3% and intraoperative peri-prosthetic fracture rate of 2.4% with use of an uncollared uncemented stems.…”
Section: Introductionmentioning
confidence: 99%
“…5 There is evidence that its use in the elderly, who are likely to have osteoporotic bone, is acceptable, with good osseo-integration and little subsidence. 6,7 A radiostereometric analysis 8 has demonstrated a mean subsidence of 2.7 mm when the Corail stem is used to treat intracapsular fractures. There are collared and collarless versions, with the collar designed to prevent excess subsidence.…”
mentioning
confidence: 99%